2020
DOI: 10.32479/ijeep.8510
|View full text |Cite
|
Sign up to set email alerts
|

Does Formal Constraints Reduce Co2 Emissions? Indonesia’s Empirical Case

Abstract: Rules (formal constraints) are expected to be able to shape human behavior to act based on what should and should not do accordingly. The connection of rules in the energy sector to carbon dioxide emissions depends on how far the rules are able to shape behavior as expected. The purpose of this study is to analyze the effect of rules (formal constraints) on CO 2 emissions in Indonesia. Other variables used in this study are energy consumptions (fossil energy and renewable energy), and population growth which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…How does the implementation of the law compare to the public and industry and what is the impact between them? (Darwanto et al, 2020) How and to what extent are emerging fiscal plans facilitating the transition to low-carbon energy and achieving the country's energy goals, including energy access, security and the environment? (A.…”
Section: Renewable Energymentioning
confidence: 99%
“…How does the implementation of the law compare to the public and industry and what is the impact between them? (Darwanto et al, 2020) How and to what extent are emerging fiscal plans facilitating the transition to low-carbon energy and achieving the country's energy goals, including energy access, security and the environment? (A.…”
Section: Renewable Energymentioning
confidence: 99%
“…The results showed that the only country experiencing the Environmental Kuznets Curve (EKC) trend is Singapore because of the inverted U curve that is in line with Katircioğlu (2014). While Malaysia, Thailand and Indonesia began to experience emissions reductions, which were strengthened by Darwanto et al (2019); Ridzuan et al (2020) in the long run the curve will decrease. Brunei Darussalam and the Philippines tend to be flat volatile.…”
Section: Descriptivementioning
confidence: 99%
“…Some of the problems of BUMDesa include communication problems between management, business unit management, personnel problems, and village potentials that have not been utilized [5]. Issues in managing BUMDesa in several areas include the type of business that is run is still limited, limited human resources that manage BUMDesa, and low community participation due to their insufficient knowledge [6]. The BUMDesa business unit has not been able to empower the community and reduce the unemployment rate because the total absorption of labor from the BUMDesa business units is still tiny [7].…”
Section: Introductionmentioning
confidence: 99%